A Test-Retest Study of Single- and Multi-Delay pCASL for Choroid Plexus Perfusion Imaging in Healthy Subjects Aged 19 to 87 Years - Zixuan Liu; Qinyang Shou; Kay Jann; Chenyang Zhao; Danny JJ Wang; Xingfeng Shao (NeuroImage)
There is a growing interest in the choroid plexus (ChP) due to its critical role in cerebrospinal fluid (CSF) production and its involvement in neurodegenerative and cerebrovascular diseases. However, comprehensive studies comparing the accuracy and reliability of single- and multi-PLD (post-labeling delay) arterial spin labeling (ASL) techniques, specifically in relation to the ChP, remain limited. This study systematically evaluated the test-retest reliability and quantification accuracy of cerebral blood flow (CBF) measurements, focusing on the ChP, using single-delay and multi-delay 3D gradient-and-spin echo (GRASE) pseudo-continuous ASL (pCASL) on 28 subjects (aged 19 to 87 years, 14 males/14 females) at 3.0 tesla. Both single-delay (2 s) and 5-PLD (0.5 – 2.5 s) pCASL scans were repeated approximately one week apart with a spatial resolution of 2.5 × 2.5 × 3 mm³. Voxel-wise and regional CBF and arterial transit time (ATT) measurements were compared to assess test-retest reliability, with a particular focus on ChP perfusion changes with age. In this study, 12.15 % of ChP voxels exhibited ATTs longer than 2 s, potentially leading to a significant underestimation of CBF using single-delay ASL. Multi-delay ASL showed improved accuracy in estimating CBF values for the ChP compared to single-delay ASL when ATT > PLD. Additionally, ChP volume (mean ± std = 1.72± 0.85 ml) increased (p < 0.01) and ChP perfusion (43.07±14.18 mL/100 g/min) decreased (p = 0.04) with age. These findings underscore the robustness of multi-delay ASL with model-fitting quantification in assessing ChP perfusion, making it the preferred method for accurate CBF and ATT estimation, particularly in regions with prolonged transit time such as ChP.